2010
DOI: 10.3322/caac.20066
|View full text |Cite
|
Sign up to set email alerts
|

American Cancer Society Guideline for the Early Detection of Prostate Cancer: Update 2010

Abstract: In 2009, the American Cancer Society (ACS) Prostate Cancer Advisory Committee began the process of a complete update of recommendations for early prostate cancer detection. A series of systematic evidence reviews was conducted focusing on evidence related to the early detection of prostate cancer, test performance, harms of therapy for localized prostate cancer, and shared and informed decision making in prostate cancer screening. The results of the systematic reviews were evaluated by the ACS Prostate Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
727
2
23

Year Published

2011
2011
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 820 publications
(771 citation statements)
references
References 161 publications
(222 reference statements)
19
727
2
23
Order By: Relevance
“…While screening recommendations vary somewhat by professional organization [5][6][7], the U.S. Preventive Services Task Force now recommends against routine screening for all ages [8]. In the midst of this debate, most men undergoing PCa screening are aware of the benefits, but fewer are aware of the limitations [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While screening recommendations vary somewhat by professional organization [5][6][7], the U.S. Preventive Services Task Force now recommends against routine screening for all ages [8]. In the midst of this debate, most men undergoing PCa screening are aware of the benefits, but fewer are aware of the limitations [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, attention has been directed toward creating algorithms or nomograms that combine multiple clinical and laboratory features into risk scores to help in clinical decision making. [5][6][7][8] Nomograms are risk assessment tools that combine multiple clinical and laboratory risk factors to inform clinical decision making about biopsy, risk classification, and/or treatment options. Although there is wide variation in the manner in which the algorithms and nomograms have been developed and validated, a recent systematic review suggested that these tools tend to provide more accurate diagnostic predictions for cancer-positive biopsies than the use of PSA testing or other factors alone.…”
Section: Background and Clinical Context For The Recommendationmentioning
confidence: 99%
“…In the U.S. and Europe, guidelines recommend that clinicians begin offering PSA screening to men between 40 and 50 years of age [13][14][15][16]. Data from the ERSPC demonstrated a clear mortality benefit of PSA screening in men 55-59 years of age [7], as well as those 60-64 years of age [9••].…”
Section: Who Is At Risk?mentioning
confidence: 99%